2019
DOI: 10.1093/sleep/zsz102
|View full text |Cite
|
Sign up to set email alerts
|

Visual experience drives sleep need in Drosophila

Abstract: Sleep optimizes waking behavior, however, waking experience may also influence sleep. We used the fruit fly Drosophila melanogaster to investigate the relationship between visual experience and sleep in wild-type and mutant flies. We found that the classical visual mutant, optomotor-blind (omb), which has undeveloped horizontal system/vertical system (HS/VS) motion-processing cells and are defective in motion and visual salience perception, showed dramatically reduced and less consolidated sleep compared to wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 59 publications
0
16
0
Order By: Relevance
“…To increase sleep in upd2 mutants, we used a sleep-promoting drug, THIP (4,5,6,7- tetrahydroisoxazolo-[5,4-c]pyridine-3-ol). Previous work has shown that THIP-induced sleep restores behavioral plasticity and attention to Drosophila mutants [ 28 , 78 ], so we were curious if increased sleep in upd2 knockdown animals would return distractibility to control levels, which would argue that the increased fixation observed in these animals was a failure of attention corrected by sufficient sleep. As expected, THIP exposure increased sleep in upd2 knockdown animals ( Fig 7A , compare with Fig 2C ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To increase sleep in upd2 mutants, we used a sleep-promoting drug, THIP (4,5,6,7- tetrahydroisoxazolo-[5,4-c]pyridine-3-ol). Previous work has shown that THIP-induced sleep restores behavioral plasticity and attention to Drosophila mutants [ 28 , 78 ], so we were curious if increased sleep in upd2 knockdown animals would return distractibility to control levels, which would argue that the increased fixation observed in these animals was a failure of attention corrected by sufficient sleep. As expected, THIP exposure increased sleep in upd2 knockdown animals ( Fig 7A , compare with Fig 2C ).…”
Section: Resultsmentioning
confidence: 99%
“…Sleep in flies has been shown to fulfill key criteria for identifying sleep in other animals, such as increased arousal thresholds and homeostatic regulation [ 24 , 25 ], so the fly is a promising avenue for understanding sleep and feeding regulation at a circuit level. Additionally, cognitive readouts such as visual attention paradigms are increasingly available for Drosophila research [ 26 28 ], providing relevant functional assessments of manipulations that could impact sleep and feeding.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, ring neurons might require resetting through sleep sooner than other transiently active neurons and might therefore be responsible for signaling sleep drive. We additionally did not differentiate between different ring attractor inputs (for example visual or idiothetic) and such different signals could also be integrated in different ring neurons or homeostats 11 (taking for example into account that visual experience increases sleep need 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…Visual information processed by motion circuits play an important role in sleep regulation. Flies lacking HS and VS neurons ( omb H 31 mutants) display a reduced and fragmented sleep compared to wild-type (wt), while the optogenetic activation of these cells results in an increase of nighttime sleep ( Kirszenblat et al, 2019 ). Moreover, the optogenetic activation of T5 neurons leads to a consolidation of nighttime sleep, with increased bout duration and lower bouts number ( Kirszenblat et al, 2019 ; Figure 4 ).…”
Section: How Do Light Inputs Modulate Sleep In Drosophila mentioning
confidence: 99%
“…Histamine released by light-activated photoreceptors likely acts in at least two different pathways directly involved in sleep regulation: the visual (photic) input and the motion detection pathways, distinct signalling dynamics both relying on activation of lamina interneurons L2 ( Meinertzhagen and O’Neil, 1991 ; Meinertzhagen and Sorra, 2001 ; Shinomiya et al, 2014 , 2019 ; Muraro and Ceriani, 2015 ; Kirszenblat et al, 2019 ; Borst et al, 2020 ; Figure 4 ).…”
Section: How Do Light Inputs Modulate Sleep In Drosophila mentioning
confidence: 99%